Avaliação do atendimento educacional especializado (AEE) como política pública de inclusão nas escolas do município de Horizonte - CE - Morais, Francisca Renata Chaves de (2024)
In recent years, Brazil has made significant progress in inclusive education through the implementation of the National Policy on Special Education from the Perspective of Inclusive Education in 2008. This policy emphasizes the importance of providing resources and strategies that ensure equal access and opportunities for all students, including those with disabilities. Measures such as Multifunctional Resource Rooms and Specialized Educational Services were introduced to support this inclusive approach. Theorists such as Mantoan (2008), Baptista (2013), and Bedaque (2014) have extensively discussed how these changes require a significant transformation in educators' practices and school infrastructure to accommodate all students' needs. Considering the above, the general objective of this research is to evaluate Specialized Educational Assistance (AEE) as a public policy of inclusion in the teaching and learning process of students with disabilities in the schools of the municipality of Horizonte - CE, in light of Rodrigues' (2008) in-depth evaluation in the dimensions of content, context, trajectory, temporality, and territoriality of the policy. Regarding methodology, the research is qualitative in nature and, in terms of objectives, is characterized as exploratory and descriptive, using a case study strategy (Gil, 2008; Yin, 2001). Data collection techniques will include bibliographic research, document analysis, and semi-structured interviews (Minayo, Deslandes, and Gomes, 2009). The analysis of the collected data will be conducted through document analysis and discourse analysis (Rodrigues, 2008; Orlandi, 2009). The results indicate the following findings: (i) the research identified a disconnect between formally adopted public policies and their practical implementation in schools; (ii) structural and resource challenges prevent the AEE from fully meeting students' needs, including a lack of adequate space and long waiting lists; (iii) recognition and validation of the AEE as an important instrument for the teaching and learning processes of students with disabilities; (iv) positive collaboration was identified between different sectors, such as the Centro de Nazaré Domingos and the CACE, which offer crucial multidisciplinary support for the special education policy from an inclusive perspective.